1986
DOI: 10.1289/ehp.8665351
|View full text |Cite
|
Sign up to set email alerts
|

Indirect health effects of relative humidity in indoor environments.

Abstract: A review of the health effects of relative humidity in indoor environments suggests that relative humidity can affect the incidence of respiratory infections and allergies. Experimental studies on airborne-transmitted infectious bacteria and viruses have shown that the survival or infectivity of these organisms is minimized by exposure to relative humidities between 40 and 70%. Nine epidemiological studies examined the relationship between the number of respiratory infections or absenteeism and the relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(193 citation statements)
references
References 80 publications
6
172
1
6
Order By: Relevance
“…The optimal parameters of RH for health are defined by Arundel et al as 40%-60% humidity; beyond this range, RH can impact on respiratory infections and allergies, by reducing the infectivity of airborne-transmitted infectious bacteria and viruses [44]. In Passive House design, the RH optimal comfort range is 35%-55%, for the avoidance of "mould and the fast growth of HDM" [19] (p. 6).…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…The optimal parameters of RH for health are defined by Arundel et al as 40%-60% humidity; beyond this range, RH can impact on respiratory infections and allergies, by reducing the infectivity of airborne-transmitted infectious bacteria and viruses [44]. In Passive House design, the RH optimal comfort range is 35%-55%, for the avoidance of "mould and the fast growth of HDM" [19] (p. 6).…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…Chamber experiments using clean air showed no drying out of the mucosa after exposure to 9% relative humidity for 78 hours [30]. However, Green [31] and Arundel [32] found that dry indoor air could impair the ciliary function, resulting in an increased occurrence of respiratory infections. RH about 40% has been suggested to be better for the eyes and the airways than levels below 30% [33].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor microbial communities are an important component of everyday human health37, and are even partially composed of human-associated bacteria1 due to the high emission rate of up to 10 6 bacteria per person-hour8. In ICUs, sanitation protocols are stricter than in other areas of the hospital, yet many patients treated in ICUs are infected with hospital-acquired “nosocomial infections” often due to an underlying severe disease910.…”
mentioning
confidence: 99%